1981
DOI: 10.1093/nar/9.4.947
|View full text |Cite
|
Sign up to set email alerts
|

Selection and analysis of cloned developmentally-regulated Dictyostelium discoideum genes by hybridization-competition

Abstract: We describe a new technique for selection of cloned gene segments which are expressed preferentially at one developmental stage but at a relatively low level. A nitrocellulose filter replica of plaques of lambda phage which contain approximately 8 KB inserts of genomic DNA is prepared; it is hybridized with a small amount of [32p] labeled mRNA prepared from one developmental stage, in the presence of a several-hundred fold excess of competitor RNA from a different stage. We show that clones of Dictyostelium nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…In Further complications may arise from repeat sequences in different mRNAs. These have been shown to exist in slime molds (18,41) and possibly affect the selection procedures (22). Our selection procedures included higher criteri- Quantitative measurements of the steadystate concentrations showed that individual pluteus-specific mRNAs accumulated to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…In Further complications may arise from repeat sequences in different mRNAs. These have been shown to exist in slime molds (18,41) and possibly affect the selection procedures (22). Our selection procedures included higher criteri- Quantitative measurements of the steadystate concentrations showed that individual pluteus-specific mRNAs accumulated to different extents.…”
Section: Discussionmentioning
confidence: 99%
“…Labeling of DNA (nick-translation), gel fractionation of RNA and DNA, and blotting onto nitrocellulose filters were performed as described (7,8). Prehybridization, hybridization, and washing of filters were conducted exactly as described (5).…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of Genomic Clones. The Dictyostelium EcoRI genomic library in A gt-XWEs has been described (8). The Charon 28 library was constructed by ligating partially digested Sau3A genomic framents to the BamHI site of the vector (9) and will be described in detail elsewhere (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…The filters were prehybridized in a solution containing 5x SSC, 3x Denhardt solution, 0.2% SDS, and 50 pg of E. For the preparation of the RNA filters denatured poly(A+) RNA was fractionated on 1.5% agarose gels containing 6% formaldehyde as described by Rave et al (23). The RNA was then transferred to nitrocellulose paper as described by Mangiarotti et al (17). The filters were hybridized as described for the DNA dot-blot filters with denatured plasmid DNA that had been radioactively labeled by nick translation (106 Cerenkov cpm per ml of hybridization buffer; 8 x 106 Cerenkov cpm per ,ug of DNA) (19,24 8, and 9), 10 h (lanes 10, 11, and 12), or 15 h (lanes 13,14, and 15) after transfer to sporulation medium (SPO).…”
Section: Methodsmentioning
confidence: 99%